The palm oil dilemma: Policy tensions among higher productivity, rising demand, and deforestation - Wiebe, Keith D.; Sulser, Timothy B.; Pacheco, P.; Pinto, A. de; Mason-D'Croz, Daniel; Dermawan, A.; Thomas, Timothy S.; Li, M.; Robinson, Sherman; Dunston, S. (International Food Policy Research Institute, 2019)
Palm oil production has increased rapidly over the past two decades in response to rising demand for its use in food, energy, and industrial applications. Expansion of oil palm plantations presents a dilemma, as they can displace forests and peatlands, leading to biodiversity losses and increased greenhouse gas emissions. Although projections show that expansion of oil palm area will slow with faster yield growth, important concerns remain that will require careful attention from policymakers.